1999
DOI: 10.1590/s0100-69911999000200008
|View full text |Cite
|
Sign up to set email alerts
|

Infecção de sítio cirúrgico: estudo prospectivo de 2.149 pacientes operados

Abstract: A atual caracterização de infecção do sítio cirúrgico em incisional superficial, incisional profunda e órgão cavidade, em substituição à tradicional definição de "infecção de ferida operatória", associada a estratificação dos pacientes em grupos de risco de infecção cirúrgica de acordo com a metodologia NNISS (National Nosocomial Infection Surveillance System), permitiram a obtenção de taxas de infecção mais fidedignas e estudos comparativos entre instituições diferentes. Baseado nessa metodologia, o presente … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
3

Year Published

2003
2003
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 8 publications
0
5
0
3
Order By: Relevance
“…In the present study, the cases found with SSI were classified and proved according to the elaboration of some studies in the area. 8,[18][19][20][21][22] The prevalence of SSIs in the hospital setting was seven (8.3%) and 41 (48.8%),in the home setting, respectively. This result is considered acceptable and coincides with other studies, such as the one performed in Amazonia that found a total of 81 (3.68%) SSIs when analyzing 2,203 patients in the period from 2009 to 2010.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present study, the cases found with SSI were classified and proved according to the elaboration of some studies in the area. 8,[18][19][20][21][22] The prevalence of SSIs in the hospital setting was seven (8.3%) and 41 (48.8%),in the home setting, respectively. This result is considered acceptable and coincides with other studies, such as the one performed in Amazonia that found a total of 81 (3.68%) SSIs when analyzing 2,203 patients in the period from 2009 to 2010.…”
Section: Discussionmentioning
confidence: 99%
“…[23][24][25][26][27][28][29] The risk factors related to the development of a SSI in the postoperative period in the hospital setting which stood out in this study were cholecystectomy surgeries, acute cholecystitis diseases and cholelithiasis, and the period of hospitalization until discharge, which are corroborated in the research scientific studies. 8,21,[25][26] However, cholecystectomy and the diagnosis of acute cholecystitis were not significant or differential elements that could certify that the patients who presented these factors suffered more SSIs in the hospital setting than those who did not undergo this surgical intervention, nor were they diagnosed with the disease, 33 these results did not compromise the achievement of the objectives proposed by this research statistically.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Quanto à vigilância pós-alta, a literatura ressalta sua importância, pois os casos de infecção seriam subestimados se ela não existisse, como podemos verificar em estudos, nos quais os autores identificaram que 32,5% dos casos de infecção foram diagnosticados no ambulatório durante o retorno do paciente 19 . Em outra pesquisa, os estudiosos verificaram que 62,9% das infecções do sítio cirúrgico foram notificadas no ambulatório de egressos, sendo que a maioria das infecções (89,7%) foi notificada até 21 dias após a cirurgia 20 .…”
Section: Discussionunclassified
“…Em um estudo detectou-se também maior incidência de infecção considerada incisional superficial, os autores da investigação ressaltaram a importância da vigilância pós-alta, pois 32,5% dos casos de infecção detectados foram identificados no ambulatório durante o retorno do paciente; entretanto, não constava no artigo qual o período de acompanhamento do paciente após a realização do procedimento cirúrgico. (15) Na Tabela 5 demonstramos os fatores de risco de infecção do sítio cirúrgico encontrados nos 18 casos de infecção detectados neste estudo.…”
Section: Fatores Relacionados à Incisão Cirúrgicaunclassified